Influence of soaking 30% and 50% baking soda (sodium bicarbonate) solution for 5, 10, and 15 days towards tooth dicolorisation - Diyah Fatmasari; Ratnawati Hendari; Irma H.Y Siregar (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2014)
ABSTRACT One cause of teeth apperance disruption is teeth discoloritation. Tooth disclorisation caused by intrinsic, extrincic and aged related factor. Several ways to change yellow teeth become white teeth. Baking soda is one of such material which can whiten teeth. Recent research aims to find 30% and 50% baking soda solution effectiveness towards teeth discolorisation.Experimental with pre-post group design was used as research design. Baking soda solution was made with two different concentration (30 and 50%), then teeth was measured the white level with shade guide. Samples then soaked in baking soda solution for 5, 10, and 15 days. Every 5 days the teeth was re-measured the white level until 15 days. Research results shown baking soda solution 50% is more effective to whiten teeth than baking soda solution 30%. Further research about baking soda for whiten teeth is needed. Key words : Baking Soda, soaked, tooth discoloritation